The Mitochondrial Genome–on Selective Constraints and Signatures at the Organism, Cell, and Single Mitochondrion Levels - Shtolz, Noam; Mishmar, Dan (Frontiers in Ecology and Evolution, 2019)
Natural selection acts on the phenotype. Therefore, many mistakenly expect to observe its signatures only in the organism, while overlooking its impact on tissues, cells and subcellular compartments. This is particularly crucial in the case of the mitochondrial genome (mtDNA) which unlike the nucleus resides in multiple cellular copies, that may vary in sequence (heteroplasmy) and quantity among tissues. Since the mitochondrion is a hub for cellular metabolism, ATP production, and additional activities such as nucleotide biosynthesis and apoptosis, mitochondrial dysfunction leads to both tissue-specific and systemic disorders. Therefore, strong selective pressures act to maintain mitochondrial function via removal of deleterious mutations via purifying (negative) selection. In parallel, selection also acts on the mitochondrion to allow adaptation of cells and organisms to new environments and physiological conditions (positive selection). Nevertheless, unlike the nuclear genetic information, the mitochondrial genetic system incorporates closely interacting bi-genomic factors (i.e. encoded by the nuclear and mitochondrial genomes). This is further complicated by the order of magnitude higher mutation rate of the vertebrate mtDNA as compared to the nuclear genome. Such mutation rate difference generates a generous mtDNA mutational landscape for selection to act, but also requires tight mito-nuclear co-evolution to maintain mitochondrial activities. In this essay we will consider the unique mitochondrial signatures of natural selection at the organism, tissue, cell and single mitochondrion levels.